2014
DOI: 10.1039/c3py01356a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of thermo-responsive polypeptoid bottlebrushes

Abstract: Linear polypeptoid macromonomers with controlled chain length and composition were prepared by norbornene methylamine-initiated copolymerization of N-ethyl N-carboxyanhydride (Et-NCA) and Nbutyl N-carboxyanhydride (Bu-NCA). Polypeptoid bottlebrush copolymers with varying backbone length and side chain composition were subsequently synthesized using the grafting-through method via the ring-opening metathesis polymerization (ROMP) of norbornenyl-terminated poly(N-ethyl glycine)-ranpoly(N-butyl glycine) macromono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 42 publications
0
47
0
Order By: Relevance
“…[290], polylactate groups [291,292,293], polypeptide chains [294], polyacrylate or substituted polystyrene chains [295], nitroxide groups [296], fluorescent groups [297], a perfluorooctyl group [298], perfluorocarboxylic acid groups [299], and a fullerene-carbene adduct [300]; (2) norbornene in the presence of Fe 3 O 4 nanoparticles [301]; (3) norbornenes in the presence of an allylated lanthanide salen complex [302]; (4) norbornyl-acac-like systems complexed to terbium [303] or to an iridium-pyrazolone complex (e.g. 71) [304];…”
Section: Polymerization Reactionsmentioning
confidence: 99%
“…[290], polylactate groups [291,292,293], polypeptide chains [294], polyacrylate or substituted polystyrene chains [295], nitroxide groups [296], fluorescent groups [297], a perfluorooctyl group [298], perfluorocarboxylic acid groups [299], and a fullerene-carbene adduct [300]; (2) norbornene in the presence of Fe 3 O 4 nanoparticles [301]; (3) norbornenes in the presence of an allylated lanthanide salen complex [302]; (4) norbornyl-acac-like systems complexed to terbium [303] or to an iridium-pyrazolone complex (e.g. 71) [304];…”
Section: Polymerization Reactionsmentioning
confidence: 99%
“…[19] Bottlebrush copolymers comprised of the linear P(NEG-r-NBG) random copolypeptoid sidechains were obtained by ROMP of the norbornene-terminated P(NEG-r-NBG) macromonomer ( Figure 5). [71] The polypeptoid bottlebrush copolymers also exhibited cloud point transition in aqueous solution similarly to the linear macromonomers.…”
Section: Thermal Properties Of Polypeptoidsmentioning
confidence: 99%
“…[71] Freshly prepared aque- proline) copolymer can be hydrolytically degraded into the respective amino acids under highly acidic conditions (6N HCl, 1208C, 24 h). [82] We have found that polysarcosine also completely degraded into the blocks with higher content of the sarcosine at the N-terminus.…”
Section: Thermal Properties Of Polypeptoidsmentioning
confidence: 99%
“…While these terms provide a great framework for understanding and explaining certain experimental observations, a more quantitative approach is frequently desired. 1,2 Given universal interest in "hydrophobic" surfaces, 2,3 monomers, 4-6 micelles, 7 polymers, 8,9 peptides, 10 proteins, 11 molecules, 12 solvents, 13 and drugs, 14 comparing one system to another is often necessary.…”
Section: Introductionmentioning
confidence: 99%